Electronic ballast - Husain, Nik Muhammad Fashan (2007)
Nowadays, the development in technology causes some intelligent groups to create many ideas in producing something useful for human life. The increasing of electrical cost will give more advantages to the engineers to make research in producing the electrical equipments that can save electrical energy. One of application is electronic ballast. The electronic ballast is targeting the most of peoples because everyone needs the electrical energy for lighting system whether at home, office, school, mosque, factory and so on. The electronic ballast specially made to replace the conventional choke in fluorescent lamp. Electronic ballast can control the lamp power more easily and has higher efficiency since it uses the power semiconductor devices with better switching method. Even the cost for produce the electronic ballast is more expensive than conventional choke, it still has more advantage in lifetime operation because it is greater than conventional choke. By using the 240 VAC as a voltage source, the combination of L-C circuit will be acts as filter in electronic ballast circuit to eliminate the spikes and smoothes out the steps in the current waveform during start-up.. Furthermore, the introducing of IR2156 ballast controller IC in electronic ballast circuit can make the operation of lighting system will improved. The IR2156 IC has include the programmable preheat frequency, programmable preheat time and programmable over current protection and internal ignition ramp which can make sure the safety of this system is guaranteed. Consequently, the high frequency can obtained and the efficiency of lamp operation can improved. Therefore, everyone can save his or her money to pay the electricity bill since the electronic ballast used in fluorescent lamp.